Pola ruang natah di Desa Sibang Gede, Kecamatan Abiansemal, Kabupaten Badung, Provinsi Bali - Nugraha, Komang Teja; Sudarsana, Anak Agung Gede Dalem; Sugiantara, Anak Agung Gede (Jurnal Arsitektur Lansekap; Vol.4, No.1, April 2018, 2018)
Space pattern of natah at Sibang Gede Village, Abiansemal District, Badung Regency, Bali Province. The growth of population in Sibang Gede Village, requires a land for the construction of the house based on the philosophy of Balinese culture concept. The extent of these needs impact on the rearrangement of space and the function of buildings and plants that make the space of Balinese traditional home pattern is not applied properly. This research aims to determine the layout and function of each buildings and plants. The method used was survey method with observation technique, interview, literature study and questionnaire distribution. From 12 banjar adat (sub-village) taken each of the four yards as sample by random sampling. The results show that 60% of the people at Sibang Gede Village still did not know the placement of buildings based on the philosophy of Balinese culture and placement of plants based on the philosophy of Balinese culture 98% of the people at Sibang Gede Village still have not applied it. The concept philosophy of Balinese culture consists of Asta Bumi, Hulu-teben as the layout concept of the buildings and Asta Dala as arrangement concept of plants layout. The recommendation that can be given is to apply the philosophy of Balinese culture concept of the space pattern of natah.